The Crimes Of Attacks On Electronic Banks - Boukhalfa, Hadda (مجلة الباحث للدراسات الأكاديمية, 2022)
There are many forms of violations and attacks targeting electronic bank security and the means through which these attacks are carried out are renewed and varied. Behind this is the special nature of the Internet, as it is an electronic network characterized by development, which helped the abusers to easily navigate through various websites, and the ease of sending and receiving data, which threatens the security of electronic banking transactions, in addition to the financial nature of banking transactions that are coveted by abusers to assault her. This study aims to focus on the images of abuse that pose a threat to the security of the electronic bank, and they are crimes against the data of these banks' websites and the systems and software they operate.